Preparation method and application of cobalt-containing sodium ion battery positive electrode material

Through the preparation method of the composite sodium ferrophosphate pyrophosphate positive electrode material doped with cobalt ion, the problems of low specific capacity and limited electronic conductivity improvement of polyanionic positive electrode material are solved, high specific capacity and good rate performance are achieved, and the synthesis process is simplified and the cost is reduced.

CN120573671APending Publication Date: 2025-09-02DALIAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510768863.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

The existing polyanionic positive electrode materials have lower specific capacity and limited electronic conductivity improvement, and the synthesis process is complex, which increases the preparation cost.

Method used

The preparation method of a cobalt-ion-doped composite sodium ferrophosphate phosphate (Na4Fe3-xCox(PO4)2P2O7) positive electrode material is obtained by uniformly mixing the sodium source, iron source, cobalt source, phosphorus source and carbon source in isopropanol, then ball milling and drying, and then calcining under an argon atmosphere to obtain a cobalt-doped carbon-coated sodium ferrophosphate positive electrode material.

Benefits of technology

The specific capacity and rate performance of the material are improved, the material is single and the crystallinity is good, the synthesis process is simplified, the energy consumption is reduced, and it is conducive to industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion battery positive electrode materials, and discloses a preparation method and application of a cobalt-containing sodium ion battery positive electrode material. The preparation method comprises the following steps: adding a sodium source, an iron source, a cobalt source, a phosphorus source and a carbon source into isopropanol, uniformly mixing to form slurry, carrying out ball milling on the slurry, drying to obtain a precursor, and calcining in an argon atmosphere to obtain the cobalt-doped carbon-coated ferric sodium pyrophosphate (Na4Fe3-xCox (PO4) 2P2O7) positive electrode material, in which x is greater than or equal to 0 and less than or equal to 0.3. The synthesis method of the ferric sodium pyrophosphate positive electrode material provided by the invention has the advantages of simplicity in operation and low energy consumption, industrial production is facilitated, meanwhile, the synthesized material ensures the stability of a crystal structure in a Na < + > intercalation / deintercalation process, the specific capacity and the rate capability of the material are improved, and the application prospect is wide. The problems of low specific discharge capacity, poor rate capability and the like of the pyrophosphate ferric phosphate sodium material are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and the present invention relates to a method for preparing a cobalt-containing sodium ion battery positive electrode material and applications thereof. Background Art

[0002] With the rapid development of modern industry, human society's demand for energy has increased dramatically. The extensive use of traditional fossil fuels has had a series of impacts on the global climate, and due to its non-renewable nature, it has prompted changes in the energy industry. In energy storage technology, lithium-ion batteries have become one of the core technologies due to their high energy density and long service life. However, lithium resources are limited and unevenly distributed around the world, resulting in a continuous increase in the price of lithium-ion batteries, which to some extent restricts their development. Sodium and lithium belong to the same main group elements and have similar physical and chemical properties. Due to the abundance and widespread distribution of sodium resources, sodium-ion batteries have shown significant commercial potential. In addition, the working principle of sodium-ion batteries is similar to that of lithium-ion batteries, and they can draw on mature lithium-ion battery technology, further lowering the threshold for research and development and industrialization.

[0003] The cathode material is one of the core materials of sodium-ion batteries. Its composition and structure directly affect the reversible capacity and output voltage of the battery. Among polyanion cathode materials, Na4Fe3(PO4)2P2O7 is a composite of phosphate and pyrophosphate. Larger anion groups result in materials with lower specific capacity and electronic conductivity. Existing research, such as the spray drying method to synthesize spherical Na4Fe3(PO4)2P2O7 powder, although it controls the surface morphology of the material, has limited improvement in the electronic conductivity of the material performance. Moreover, the synthesis process of this method is complex, and the equipment and operation requirements are high, which increases the preparation cost. Future research needs to further improve its comprehensive performance while maintaining its low cost and environmental advantages. Summary of the Invention

[0004] In order to overcome the shortcomings of the prior art and solve the problem of low specific capacity of polyanion positive electrode materials, the present invention provides a method for preparing a cobalt-containing sodium ion battery positive electrode material and its application, which is a cobalt-doped composite sodium iron pyrophosphate (Na4Fe 3-x Co x A method for preparing a (PO4)2P2O7) cathode material. The introduction of cobalt improves the material's internal electronic energy level structure, enhancing its conductivity and, consequently, its specific capacity. This preparation method utilizes readily available raw materials and a simple, rapid synthesis process, providing guidance for the development of cathode materials for sodium-ion batteries.

[0005] The above-mentioned object of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a cobalt-containing sodium ion battery positive electrode material, the specific steps are as follows:

[0007] (1) adding a sodium source, an iron source, a cobalt source, a phosphorus source, and a carbon source to isopropyl alcohol and uniformly mixing to form a slurry, and then ball milling the slurry and drying to obtain a precursor;

[0008] (2) The precursor powder is calcined in an argon atmosphere to obtain a cobalt-doped carbon-coated sodium iron phosphate pyrophosphate positive electrode material.

[0009] Furthermore, in step (1), the sodium source is one or more of sodium pyrophosphate, sodium acetate, sodium carbonate or sodium dihydrogen phosphate; the iron source is one or more of dihydrate and ferrous oxalate, iron powder, ferric nitrate or ferric oxide; the cobalt source is one or more of cobalt oxalate dihydrate, cobalt oxide, cobalt carbonate or cobaltous hydroxide; the phosphorus source is one or more of sodium dihydrogen phosphate, sodium pyrophosphate or ammonium dihydrogen phosphate; and the carbon source is one or more of glucose monohydrate, sucrose or citric acid.

[0010] Furthermore, in step (1), the molar ratio of Na, Fe, Co, P, and C in the sodium source, iron source, cobalt source, phosphorus source, and carbon source is 4:3-x:x:4:6, where x=0 to 0.3.

[0011] Furthermore, in step (1), the ball milling speed is 400-500 r / min, the ball milling time is 10-12 h, and the solid content of the slurry after ball milling is 40-50%. Preferably, the ball milling speed is 450 r / min, and the ball milling time is 10.5 h.

[0012] Furthermore, in step (1), the slurry is dried by forced air drying or vacuum drying at a temperature of 80 to 100° C. for 10 to 12 hours. Preferably, the drying temperature is 100° C. and the drying time is 12 hours.

[0013] Furthermore, in step (2), the calcination conditions are: heating to 450-550°C at a heating rate of 2-3°C / min under inert gas protection, and constant temperature calcination at this temperature for 23-25 ​​hours. Preferably, the calcination is performed by placing the precursor in a tube furnace for calcination. The specific conditions of the tube furnace calcination are divided into two stages: the first stage is a heating rate of 2°C / min, the temperature is increased from 26°C to 500°C, and the heating time is 237 minutes; the second stage is maintained at 500°C for 24 hours. The atmosphere used throughout the process is argon.

[0014] The present invention also seeks to protect the use of the cobalt-containing sodium ion battery positive electrode material prepared by the above preparation method in the preparation of a sodium ion battery positive electrode.

[0015] The specific application involves grinding the prepared positive electrode material, mixing it with the binder polyvinylidene fluoride and conductive carbon black in appropriate proportions, adding N-methylpyrrolidone, stirring, and coating it on aluminum foil to form a positive electrode sheet. After drying the positive electrode sheet, a sodium sheet is used as the negative electrode to assemble a half-cell.

[0016] Furthermore, the mass ratio of the positive electrode material: polyvinylidene fluoride: conductive carbon black is 8:1:1.

[0017] Furthermore, the amount of N-methylpyrrolidone used is not particularly limited, and the powders can be mixed evenly; the coating thickness is 100 μm, and the thickness of the aluminum foil used is 12 μm.

[0018] The beneficial effects of the present invention compared with the prior art are:

[0019] (1) The present invention provides a Na4Fe 3-x Co x (PO4)2P2O7 positive electrode material, this material has a single phase, good crystallinity and excellent electrochemical properties.

[0020] (2) The present invention changes the ion channel environment by doping a small amount of Co, and the structure is stable, wherein Na4Fe 2.8 Co 0.2 The specific capacity of (PO4)2P2O7 reached 105.07mAh / g at a rate of 0.1C, and still maintained a specific capacity of 56.10mAh / g at a high rate of 30C, indicating that doping effectively improved the rate performance of the material.

[0021] (3) Na4Fe prepared by the present invention 3-x Co x The (PO4)2P2O7 positive electrode material is directly prepared by solid-phase ball milling and is easy to industrialize and mass-produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 X-ray diffraction patterns of 0.2-NFCPP prepared in Example 1, NFPP prepared in Comparative Example 1, 0.1-NFCPP prepared in Comparative Example 2, 0.3-NFCPP prepared in Comparative Example 3, and H0.2-NFCPP prepared in Comparative Example 4;

[0023] Figure 2 Scanning electron micrographs of 0.2-NFCPP prepared in Example 1 of the present invention (Figure a) and NFPP prepared in Comparative Example 1 (Figure b);

[0024] Figure 3Comparison of the specific capacities of batteries prepared using the 0.2-NFCPP prepared in Example 1, the NFPP prepared in Comparative Example 1, the 0.1-NFCPP prepared in Comparative Example 2, the 0.3-NFCPP prepared in Comparative Example 3, and the H0.2-NFCPP prepared in Comparative Example 4 positive electrode materials under 0.1C rate charge and discharge conditions;

[0025] Figure 4 The specific capacity of the battery prepared for the specific application of 0.2-NFCPP prepared in Example 1 of the present invention at different rates. DETAILED DESCRIPTION

[0026] The present invention is described in detail below by specific examples, but the scope of protection of the present invention is not limited. Unless otherwise specified, the experimental methods adopted in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.

[0027] The present invention adds sodium source, iron source, cobalt source, phosphorus source and carbon source into isopropyl alcohol and mixes them uniformly to form a slurry. The slurry is ball-milled and dried to obtain a precursor. The precursor is calcined under an argon atmosphere to obtain cobalt-doped carbon-coated sodium iron phosphate (Na4Fe 3-x Co x (PO4)2P2O7) positive electrode material, wherein 0≤x≤0.3. The synthesis method of sodium iron phosphate pyrophosphate positive electrode material provided in this application has the advantages of simple operation and low energy consumption, which is conducive to the realization of industrial production. At the same time, the synthesized material ensures Na + The stability of the crystal structure during the embedding / ejection process improves the specific capacity and rate performance of the material, effectively solving the problems of low discharge specific capacity and poor rate performance of sodium iron pyrophosphate materials.

[0028] The present invention provides a method for preparing a cobalt-containing sodium ion battery positive electrode material, and the specific steps are as follows:

[0029] (1) adding a sodium source, an iron source, a cobalt source, a phosphorus source, and a carbon source to isopropyl alcohol and uniformly mixing them to form a slurry, and then ball milling the slurry and drying it to obtain a precursor;

[0030] (2) The precursor powder is calcined in an argon atmosphere to obtain a cobalt-doped carbon-coated sodium iron phosphate pyrophosphate positive electrode material.

[0031] In step (1), the sodium source is one or more of sodium pyrophosphate, sodium acetate, sodium carbonate or sodium dihydrogen phosphate; the iron source is one or more of dihydrate and ferrous oxalate, iron powder, ferric nitrate or ferric oxide; the cobalt source is one or more of cobalt oxalate dihydrate, cobalt oxide, cobalt carbonate or cobaltous hydroxide; the phosphorus source is one or more of sodium dihydrogen phosphate, sodium pyrophosphate or ammonium dihydrogen phosphate; and the carbon source is one or more of glucose monohydrate, sucrose or citric acid.

[0032] In step (1), the molar ratio of Na, Fe, Co, P and C in the sodium source, iron source, cobalt source, phosphorus source and carbon source is 4:3-x:x:4:6, where x=0 to 0.3.

[0033] Specifically, the preparation steps are as follows:

[0034] (1) Sodium pyrophosphate (Na4P2O7), ammonium dihydrogen phosphate (NH4H2PO4), glucose monohydrate (C6H 12 O6·H2O), ferrous oxalate dihydrate (FeC2O4·2H2O), and cobalt oxalate dihydrate (CoC2O4·2H2O) were dispersed in isopropanol according to the stoichiometric ratio and ball milled.

[0035] (2) The mixed yellow slurry is placed in an oven and dried to obtain a yellow precursor.

[0036] (3) The yellow precursor is placed in a tube furnace and calcined to obtain a black solid, which is the target product.

[0037] (4) Grind the black solid and mix it with the binder polyvinylidene fluoride and conductive carbon black in a certain proportion, add N-methylpyrrolidone, stir and then coat it on aluminum foil.

[0038] (5) After drying the electrode, assemble it into a half-cell with the sodium sheet as the negative electrode.

[0039] The present invention is described below through specific embodiments and application examples.

[0040] Example 1

[0041] (1) Weigh 0.01 mol sodium pyrophosphate, 0.02 mol ammonium dihydrogen phosphate, 0.005 mol glucose monohydrate, 0.028 mol ferrous oxalate dihydrate, and 0.002 mol cobalt oxalate dihydrate and place them in a ball mill;

[0042] (2) Add 15 g of isopropyl alcohol and ball mill at 450 r / min for 10.5 h to obtain a yellow slurry;

[0043] (3) Dry the yellow slurry in an oven at 100°C for 12 h to obtain yellow precursor A;

[0044] (4) Precursor A was ground and placed in a corundum boat, heated from 26°C to 500°C at 2°C / min in an argon atmosphere in a tube furnace, and calcined at 500°C for 24 h;

[0045] (5) After cooling naturally, the mixture was taken out and ground into a black powder, which was recorded as 0.2-NFCPP.

[0046] Comparative Example 1

[0047] On the basis of Example 1, no cobalt element is added, specifically as follows:

[0048] (1) Weigh 0.01 mol sodium pyrophosphate, 0.02 mol ammonium dihydrogen phosphate, 0.005 mol glucose monohydrate, and 0.03 mol ferrous oxalate dihydrate and place them in a ball mill;

[0049] (2) Add 15 g of isopropyl alcohol and ball mill at 450 r / min for 10.5 h to obtain a yellow slurry;

[0050] (3) Dry the yellow slurry in an oven at 100°C for 12 h to obtain yellow precursor A;

[0051] (4) Precursor A was ground and placed in a corundum boat, heated from 26°C to 500°C at 2°C / min in an argon atmosphere in a tube furnace, and calcined at 500°C for 24 h;

[0052] (5) After cooling naturally, the mixture was taken out and ground into a black powder, which was recorded as NFPP.

[0053] Comparative Example 2

[0054] On the basis of Example 1, the proportion of cobalt element was reduced as follows:

[0055] (1) Weigh 0.01 mol sodium pyrophosphate, 0.02 mol ammonium dihydrogen phosphate, 0.005 mol glucose monohydrate, 0.029 mol ferrous oxalate dihydrate, and 0.001 mol cobalt oxalate dihydrate and place them in a ball mill;

[0056] (2) Add 15 g of isopropyl alcohol and ball mill at 450 r / min for 10.5 h to obtain a yellow slurry;

[0057] (3) Dry the yellow slurry in an oven at 100°C for 12 h to obtain yellow precursor A;

[0058] (4) Precursor A was ground and placed in a corundum boat, heated from 26°C to 500°C at 2°C / min in an argon atmosphere in a tube furnace, and calcined at 500°C for 24 h;

[0059] (5) After cooling naturally, the mixture was taken out and ground into a black powder, which was recorded as 0.1-NFCPP.

[0060] Comparative Example 3

[0061] On the basis of Example 1, the proportion of cobalt element was increased, specifically as follows:

[0062] (1) Weigh 0.01 mol sodium pyrophosphate, 0.02 mol ammonium dihydrogen phosphate, 0.005 mol glucose monohydrate, 0.027 mol ferrous oxalate dihydrate, and 0.003 mol cobalt oxalate dihydrate and place them in a ball mill;

[0063] (2) Add 15 g of isopropyl alcohol and ball mill at 450 r / min for 10.5 h to obtain a yellow slurry;

[0064] (3) Dry the yellow slurry in an oven at 100°C for 12 h to obtain yellow precursor A;

[0065] (4) Precursor A was ground and placed in a corundum boat, heated from 26°C to 500°C at 2°C / min in an argon atmosphere in a tube furnace, and calcined at 500°C for 24 h;

[0066] (5) After cooling naturally, the mixture was taken out and ground into a black powder, which was recorded as 0.3-NFCPP.

[0067] Comparative Example 4

[0068] On the basis of Example 1, the calcination conditions were changed as follows:

[0069] (1) Weigh 0.01 mol sodium pyrophosphate, 0.02 mol ammonium dihydrogen phosphate, 0.005 mol glucose monohydrate, 0.028 mol ferrous oxalate dihydrate, and 0.002 mol cobalt oxalate dihydrate and place them in a ball mill;

[0070] (2) Add 15 g of isopropyl alcohol and ball mill at 450 r / min for 10.5 h to obtain a yellow slurry;

[0071] (3) Dry the yellow slurry in an oven at 100°C for 12 h to obtain yellow precursor A;

[0072] (4) Precursor A was ground and placed in a corundum boat. The temperature was raised from 26°C to 300°C at 2°C / min in an argon atmosphere in a tube furnace and calcined at 300°C for 3 h; then the temperature was raised to 650°C at 2°C / min and calcined at 650°C for 8 h.

[0073] (5) After cooling naturally, the mixture was taken out and ground into a black powder, which was designated as H0.2-NFCPP.

[0074] Application Example 1

[0075] The solid powder 0.2-NFCPP prepared in Example 1 was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 8:1:1, 3.3 g of N-methylpyrrolidone was added and stirred for 12 h to prepare a uniform mixed slurry; the slurry was evenly coated on aluminum foil using a coating machine, dried at 80°C under vacuum for 15 h, and then cut into 0.2-NFCPP positive electrode sheets with a diameter of 13 mm.

[0076] The prepared 0.2-NFCPP cathode was assembled into a CR2032 button-type half-cell in an argon-filled glove box. A sodium metal sheet served as the anode; a Whatman GF / D glass fiber separator was used; and the electrolyte consisted of 1M NaClO₄ dissolved in EC / PC (1:1 volume ratio) containing 5% FEC. The assembled cell was charged and discharged at a current rate of 0.1C over a voltage range of 1.7-4.1V, achieving an initial specific capacity of 105.07 mAh / g.

[0077] The 0.2-NFCPP battery was tested at 0.1C, 0.2C, 0.5C, 1C, 5C, 10C, 20C, and 30C rates. The test results are as follows: Figure 4 The battery prepared with 0.2-NFCPP material prepared with the material of comparative example 2 has a specific capacity of 56.10 mAh / g at a high current of 30C, and the specific capacity is restored to 100.35 mAh / g when the rate is restored to 0.1C, indicating that the material has good rate performance.

[0078] Comparative Application Example 1

[0079] The solid powder NFPP prepared in Comparative Example 1 was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 8:1:1, 3.3 g of N-methylpyrrolidone was added and stirred for 12 hours to prepare a uniform mixed slurry; the slurry was evenly coated on aluminum foil using a coating machine, dried at 80°C under vacuum for 15 hours, and then cut into NFPP positive electrode sheets with a diameter of 13 mm.

[0080] The prepared NFPP cathode sheets were assembled into CR2032 button-type half-cells in an argon-filled glove box. A sodium metal sheet served as the anode; a Whatman GF / D glass fiber separator was used; and the electrolyte consisted of 1M NaClO₄ dissolved in a 1:1 volume ratio of EC / PC, containing 5% by molar mass of FEC. The assembled cells were charged and discharged at a current rate of 0.1C over a voltage range of 1.7-4.1V, achieving an initial specific capacity of 96.43 mAh / g.

[0081] Application Comparative Example 2

[0082] The solid powder 0.1-NFCPP prepared in Comparative Example 2 was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 8:1:1, 3.3 g of N-methylpyrrolidone was added and stirred for 12 hours to prepare a uniform mixed slurry; the slurry was evenly coated on aluminum foil using a coating machine, dried at 80°C under vacuum for 15 hours, and then cut into 0.1-NFCPP positive electrode sheets with a diameter of 13 mm.

[0083] The prepared 0.1-N-F-CPP cathode was assembled into a CR2032 button-type half-cell in an argon-filled glove box. A sodium metal sheet served as the anode; a Whatman GF / D glass fiber separator was used; and the electrolyte consisted of 1M NaClO₄ dissolved in EC / PC (1:1 volume ratio) with 5% FEC by molar mass. The assembled cell was charged and discharged at a current rate of 0.1C over a voltage range of 1.7-4.1V, achieving an initial specific capacity of 81.98 mAh / g.

[0084] Application Comparative Example 3

[0085] The solid powder 0.3-NFCPP prepared in Comparative Example 3 was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 8:1:1, 3.3 g of N-methylpyrrolidone was added and stirred for 12 hours to prepare a uniform mixed slurry; the slurry was evenly coated on aluminum foil using a coating machine, dried at 80°C under vacuum for 15 hours, and then cut into 0.3-NFCPP positive electrode sheets with a diameter of 13 mm.

[0086] The prepared 0.3-nm NFCPP cathode was assembled into a CR2032 button-type half-cell in an argon-filled glove box. A sodium metal sheet served as the anode; a Whatman GF / D glass fiber separator was used; and the electrolyte consisted of 1M NaClO₄ dissolved in EC / PC (1:1 volume ratio) with 5% FEC by molar mass. The assembled cell was charged and discharged at a current rate of 0.1C over a voltage range of 1.7-4.1V, achieving an initial specific capacity of 79.59 mAh / g for the 0.3-nm NFCPP cell.

[0087] Comparative Application Example 4

[0088] The solid powder H0.2-NFCPP prepared in Comparative Example 4 was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 8:1:1, 3.3 g of N-methylpyrrolidone was added and stirred for 12 hours to prepare a uniform mixed slurry; the slurry was evenly coated on aluminum foil using a coating machine, dried at 80°C under vacuum for 15 hours, and then cut into H0.2-NFCPP positive electrode sheets with a diameter of 13 mm.

[0089] The prepared H0.2-NFCPP cathode was assembled into a CR2032 button-type half-cell in an argon-filled glove box. A sodium metal sheet served as the anode; a Whatman GF / D glass fiber separator was used; and the electrolyte consisted of 1M NaClO₄ dissolved in EC / PC (1:1 volume ratio) with 5% FEC by molar mass. The assembled cell was charged and discharged at a current rate of 0.1C over a voltage range of 1.7-4.1V, achieving an initial specific capacity of 67.16 mAh / g for the 0.2-NFCPP cell.

[0090] The above-described embodiments are only preferred embodiments of the present invention, and are not intended to be all feasible embodiments of the present invention. Any obvious modifications made by a person skilled in the art without departing from the principles and spirit of the present invention should be considered to be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a cobalt-containing sodium ion battery positive electrode material, characterized in that: The specific steps are as follows: (1) adding a sodium source, an iron source, a cobalt source, a phosphorus source, and a carbon source to isopropyl alcohol and uniformly mixing them to form a slurry, and then ball milling the slurry and drying it to obtain a precursor; (2) The precursor powder is calcined in an argon atmosphere to obtain a cobalt-doped carbon-coated sodium iron phosphate pyrophosphate positive electrode material; the molar ratio of Na, Fe, Co, P, and C in the sodium source, iron source, cobalt source, phosphorus source, and carbon source is 4:3-x:x:4:6, x=0~0.

3.

2. The method for preparing a cobalt-containing sodium ion battery positive electrode material according to claim 1, wherein: In step (1), the sodium source is one or more of sodium pyrophosphate, sodium acetate, sodium carbonate or sodium dihydrogen phosphate; the iron source is one or more of dihydrate and ferrous oxalate, iron powder, ferric nitrate or ferric oxide; the cobalt source is one or more of cobalt oxalate dihydrate, cobalt oxide, cobalt carbonate or cobaltous hydroxide; the phosphorus source is one or more of sodium dihydrogen phosphate, sodium pyrophosphate or ammonium dihydrogen phosphate; and the carbon source is one or more of glucose monohydrate, sucrose or citric acid.

3. The method for preparing a cobalt-containing sodium ion battery positive electrode material according to claim 1, wherein: In step (1), the ball milling speed is 400-500 r / min, the time is 10-12 h, and the solid mass content of the slurry after ball milling is 40-50%.

4. The method for preparing a cobalt-containing sodium ion battery positive electrode material according to claim 1, wherein: In step (1), the slurry is dried by blast drying or vacuum drying; the drying temperature is 80-100° C.; and the drying time is 10-12 hours.

5. The method for preparing a cobalt-containing sodium ion battery positive electrode material according to claim 1, wherein: In step (2), the calcination conditions are: under the protection of inert gas, heating to 450-550° C. at a heating rate of 2-3° C. / min, and constant-temperature calcining at this temperature for 23-25 ​​hours.

6. The method for preparing a cobalt-containing sodium ion battery positive electrode material according to claim 1, wherein: In step (2), the calcination is carried out by placing the precursor in a tubular furnace for calcination. The specific conditions of the tubular furnace calcination are divided into two stages: the first stage has a heating rate of 2°C / min, the temperature rises from 26°C to 500°C, and the heating time is 237min; the second stage is maintained at 500°C for 24h.

7. Use of the cobalt-containing sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 1 to 6 in preparing a sodium ion battery positive electrode.

8. The use according to claim 7, characterized in that: The prepared positive electrode material is ground and mixed with a binder of polyvinylidene fluoride and conductive carbon black in proportion, N-methyl pyrrolidone is added, stirred, and then coated on an aluminum foil to obtain a positive electrode sheet.

9. The use according to claim 8, characterized in that: The mass ratio of positive electrode material: polyvinylidene fluoride: conductive carbon black is 8:1:1.

Citation Information

Cited By

  • Battery preparation method based on sodium pyrophosphate iron regeneration material and hard carbon regeneration material

    CN122393461A